2005
DOI: 10.1261/rna.7219805
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of 4.5S RNA in the signal recognition particle and on the 30S ribosomal subunit

Abstract: The signal recognition particle (SRP) from Escherichia coli consists of 4.5S RNA and protein Ffh. It is essential for targeting ribosomes that are translating integral membrane proteins to the translocation pore in the plasma membrane. Independently of Ffh, 4.5S RNA also interacts with elongation factor G (EF-G) and the 30S ribosomal subunit. Here we use a cross-linking approach to probe the conformation of 4.5S RNA in SRP and in the complex with the 30S ribosomal subunit and to map the binding site. The UV-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…A direct interaction between the NG domain and the SRP RNA in free SRP has been suggested by prior biochemical studies (17,18,(24)(25)(26). The NG-RNA interactions observed in S domain A are consistent with some but not all of these data.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A direct interaction between the NG domain and the SRP RNA in free SRP has been suggested by prior biochemical studies (17,18,(24)(25)(26). The NG-RNA interactions observed in S domain A are consistent with some but not all of these data.…”
Section: Discussionsupporting
confidence: 78%
“…These show different relative orientations of the NG domain at two different stages in the SRP cycle. In both the mammalian and S. solfataricus structures, SRP54 assumes a so-called ''open'' conformation, in which the NG domain and the RNA are separated by at least 20 Å. Biochemical data, however, indicate that, in free SRP, the NG domain can directly interact with SRP RNA (17,18,(24)(25)(26). To further address this discrepancy and to better delineate the structural basis of the first step in the SRP cycle, we have determined the crystal structure of the free S domain of SRP of the Archaeon Methanococcus jannaschii at 2.5-Å resolution.…”
mentioning
confidence: 99%
“…Nonetheless, these results do not address the role of the 4.5S RNA, which also stimulates GTPase activity in the SRP-FtsY complex in vitro and is essential for SRP function in vivo (Brown and Fournier 1984;Peluso et al 2001;Sagar et al 2004;Gu et al 2005). A truncated form of the 114-nucleotide (nt) RNA, including just the distal 44 nt at the hairpin end (domain IV) of the molecule, is sufficient to support cell growth ( Fig.…”
Section: Introductionmentioning
confidence: 97%
“…The SRP54/ Ffh-RNA complex is a target for intense investigations in attempts to explain its role in signal peptide binding and release. [51][52][53][54][55][56] It has been suggested that helix 8 may interact directly with the N-terminal portion of the signal peptide. 39 Recently, evidence has been provided that this region of the SRP RNA releases the autoinhibition of the mutually controlled GTPase activities between the signal-bound SRP and the SRP receptor (SR).…”
Section: Srp Rna Motifsmentioning
confidence: 99%